Recent Developments in the Synthesis of Substituted Purine Nucleosides and Nucleotides - R. Kore, Anilkumar; Yang, Bo; Srinivasan, Balasubramanian (Current Organic Chemistry, 2014)
Substituted purine nucleosides and nucleotides are considered as indispensible diagnostic tools since they find different applications in molecular genetics and next generation nucleic acid sequencing. This class of molecules also has pharmaceutical and other biological significance. Both carbon and nitrogen can be used as anchoring points for attaching various kinds of functional labels such as dyes and binding molecules. For carbon substituted nucleosides and nucleotides, C-6 is the most widely used anchoring point. Besides, C-2 and C-8 have also been used as anchoring points. For nitrogen substituted nucleosides and nucleotides, N-1, N-2, N-6, N-7 have demonstrated their abilities for anchoring different labels. This review will mainly focus on C-6 substituted nucleosides and nucleotides, followed by a brief summary of other substituted nucleosides and nucleotides. The past few decades have witnessed the tremendous progress in the chemical synthesis and manufacture of these substituted purine nucleosides and nucleotides. Different strategies such as halogenation, lithiation, nucleophilic substitution, nucleophilic aromatic substitution, transition metal catalyzed cross-coupling, alkylation, 1, 3-dipolar cycloaddition, nickel catalyzed cyclotrimerization and click chemistry have greatly accelerated this process. The main goal of this review is to summarize the available strategies in literature to synthesize substituted purine nucleosides and nucleotides and to keep the nucleic acid chemistry community updated with the most recent progress in this field.
Keywords: click chemistry